Casa Curutchet. Semblanza - Almeida Curth, Daniel (2003)
El autor narra de manera sensible su encuentro con la obra.
Keywords: LA PLATA; BUENOS AIRES (PROV); ARGENTINA; LE CORBUSIER; VIVIENDAS UNIFAMILIARES; VIVIENDAS SUBURBANAS; MOVIMIENTO MODERNO